Preliminary Investigation of the Pollution Status of Kashimbila Dam Takum, Taraba State, North Eastern Nigeria - Hikon, B. N; Obadimu, C. O; Ewenifa, O. J; Ruth, O. A (Kwaghe International Journal of Sciences and Technology, 2024)
Organochlorine pesticides (OCPs) are chemical compounds used to control or eliminate plant and animal pests. Most of these pesticides are non-degradable, leading to residue accumulation in aquatic environments, particularly in sediment and water. This is a significant concern today because aquatic organisms absorb these residues, which can cause serious health risks to humans. The study area, Kashimbila Dam in Takum, Taraba State, is surrounded by uplands where agricultural activities are conducted. Sediment and water samples were collected from Birama, Bibi, and Shingu, all along the Kashimbila Dam. Sample preparation and extraction were performed using analytical-grade chemicals, and OCP concentrations were determined using GC-MS. The study aimed to assess the distribution levels of OCP residues in water. Mirex and Hexachlorobenzene recorded the highest concentration levels, ranging from 0.932±0.036 to 1.712±0.342 mg/kg and from 0.701±0.681 to 1.350±0.002 mg/kg in water, respectively. In sediment, the concentrations ranged from 0.122±0.008 to 2.262±0.050 mg/kg for Mirex and from 0.094±0.008 to 1.176±0.001mg/kg for Hexachlorobenzene. The values obtained for Mirex and Hexachlorobenzene in all samples across the locations were above the WHO and FAO (2014) permissible limits of 0.1 and 0.5 mg/kg, respectively. The distribution levels of other OCPs, such as DDT, Dieldrin, Heptachlor, and Lindane, in all sample locations were also above the WHO and FAO (2009) permissible limits of 0.01 mg/kg for water and 1.00 mg/kg for sediment. The high values of these OCP residues could be attributed to the excessive use of pesticides on agricultural soils and fishing activities. Lindane, a contraband chemical commonly known as Gamalin-20, is used by fishermen to kill fish. The pH values of the three water samples from Kashimbila Dam were 8.32, 9.00, and 9.03 mg/l, indicating that the water body is alkaline or basic. High alkalinity is essential for the well-being of aquatic organisms. The pollution load index (PLI) of OCPs in water and the contamination factor (CF) of OCPs in sediment ranged from 0.110 to 15.050 and from 0.035 to 21.835, respectively, indicating that the pollution status of water and sediment from Kashimbila Dam ranged from moderate to highly polluted levels.